Budaya Ngopi, Tipologi, dan Strategi Kedai Kopi dalam Persaingan Bisnis - Chofiyana, Robbi’ul; Ariyani, Aminah Happy Moninthofa; Widodo, Slamet (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The increase in coffee consumption and coffee-drinking culture in Indonesia has been notable. This research aims to identify the typological characteristics of coffee shops in Gresik Regency and to understand the adaptation strategies these coffee shops employ to cope with business competition. The study adopts a qualitative approach using a case study method. The research conducted in Gresik Regency, focuses on three types of coffee shops: traditional coffee stalls, semi-modern coffee shops, and modern cafes. Data collection was carried out through interviews and observations. The informants involved in this study were the owners and managers of the coffee shops. The data were then analyzed using an interactive model. The typology of coffee shops in Gresik Regency shows diversity, including traditional coffee stalls, coffee shops blending modern styles, and modern cafes. These three types of coffee shops implement different adaptation strategies. Traditional coffee stalls and semi-modern coffee shops employ a prospector strategy to develop their business, while modern cafes use a defender strategy to maintain their reputation and consumer interest.